DEVELOPMENT OF SPA TIOTEMPORAL ARIMA MODEL OF WAVE CONDITIONS IN SOUTH CHINA SEA OF MALAYSIAN WATER - WAY, LEE HAN (2017)
Due to the high demand for maritime activities in the South China Sea, an accurate and robust statistical model of the wave condition is required. As such, this research aims to develop a spatio-temporal ARIMA model of the wave conditions in the said region. In addition to that, the statistical properties of the significant wave height time series in this region is studied and characterised. A baseline ARIMA model was proposed despite the effects of seasonal variations on the wave conditions. Hourly significant wave height data from six locations are tested. Four segments of data are selected from each time series. This is to remove the plausible effects of the El Nifio and La Nifia cycle to the time series. Wave time series are nonstationary by nature.